1988
DOI: 10.1159/000215802
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Coagulation Phenomena Associated with Prevalent Fall in Fibrinogen and Plasminogen during <i>L</i>-Asparaginase Treatment in Leukemic Children

Abstract: 12 children affected by acute lymphoblastic leukemia had higher baseline levels of Normotest, Antithrombin III activity (AT III:A) and antigen (AT IIl·Ag) than those found in the control group, due to increased liver protein synthesis, as shown by the higher values of 30511bumin. Treatment with L-asparaginase (L-Asp) induced a marked decrease in fibrinogen and plasminogen and only a slight but significant reduction in AT III:A, AT III:Ag, protein C and α2 antiplasmin levels. Platelet counts progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
3

Year Published

1990
1990
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 19 publications
2
14
0
3
Order By: Relevance
“…The protein C content at the start of ASP therapy is 147% and 137.5% for the E . Miniero et al [24] Legnani et al [35] O'Meara et al [20] This study This study coli and Erwinia group, respectively. During ASP treatment, however, we observed a steady decline in protein C levels.…”
Section: Discuss 1 0 Nmentioning
confidence: 94%
“…The protein C content at the start of ASP therapy is 147% and 137.5% for the E . Miniero et al [24] Legnani et al [35] O'Meara et al [20] This study This study coli and Erwinia group, respectively. During ASP treatment, however, we observed a steady decline in protein C levels.…”
Section: Discuss 1 0 Nmentioning
confidence: 94%
“…We hypothesized that thrombosis during L-asparaginase therapy is associated with low fibrinogen levels. In previous case series and case reports with L-asparaginase-induced thrombosis, low levels of fibrinogen and other clotting factors have occurred, resulting in the need for cryoprecipitate or fresh frozen plasma infusion [1,2,11,12]. No adult study to date has demonstrated an association of thrombosis with low fibrinogen in a large subset of patients.…”
Section: Introductionmentioning
confidence: 99%
“…L-asparaginase (L-ase) is an enzyme whose therapeutic effect in acute lymphoblastic leukaemia (ALL) GIMEMA the type obtained by E. coli (1 1, 12). Moreover, it has been reported that L-ase treatment is the cause of a widespread impairment of the haemostatic system (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) sometimes associated with thrombotic events (5,15,17,18,23,24). While these haemostatic complications are known to be rare in children (8), in adults they seem to be more frequent and more severe (7,25,26), although their real incidence has not been established.…”
Section: Introductionmentioning
confidence: 99%